Analysis of Factors that Correlated with Anemia Incidence in Pregnant Women at Working Area of the Sidomulyo Health Center Outpatient UPTD Pekanbaru City - Dince Safrina; Oktavia Dewi; Nurlisis; Mitra; Ika Putri Damayanti (Britain International for Academic Research (BIAR) Publisher, 2021)
Anemia in pregnant women is a condition of mothers with hemoglobin (Hb) less than 11gr / dl which can effect to risk of hemorrhage, stunted fetal growth (CHD), prematurity, low birth weight (LBW), and stunting and even death in pregnant women. The research aimed to analyze the factors that correlated with anemia incidence in pregnant women at working area of the Sidomulyo Health Center UPTD Outpatient Pekanbaru City. The type of research method was quantitative with cross sectional design. The population of pregnant women in the 2nd and 3rd trimesters based on secondary data from medical records for January 2019 - March 2020 were 2036 people with sample of 325 people. The sampling technique was systematic random sampling used secondary data from medical records. Data analysis ware univariate, bivariate and multivariate with regresi logistik ganda application. The results showed that 192 pregnant women with anemia (59.1%), the variables related with significantly to anemia in pregnant women at working area of the Sidomulyo Health Center UPTD Outpatient Pekanbaru City with nutrition status (POR = 40.647, parity (POR = 3.473), mother’s age (POR = 1,993). That can be concluded the dominant variable related to anemia in pregnant women at working area of the Sidomulyo Health Center UPTD Outpatient Pekanbaru City was nutrition status (POR = 40,647). It is recommended to Sidomulyo Health Center UPTD Outpatient to increase the implementation of service standard program the ANC 10 T, when the Covid pandemic nowadays increasing online promotion and prevention by using available technology.